PECULIARITIES OF GESTATION PROCESS WITH THREATENED MISCARRIAGE AND ITS CORRECTION - Kornienko, V.G. (World of Medicine and Biology, 2018)
Certain positive outcomes have been achieved recently in prevention and treatment of miscarriages. However, the rate of this pathology not only failed to decrease but also tends to increase. Current approaches to diagnostics and choice of adequate therapy for preventing the onset of preterm labour promote further progress of pregnancy, developing foetus in a safe intrauterine environment. The effectiveness of therapy with phytometabolic preparations for improving gestation process in women with threatened preterm labour was studied. Women from two main groups and the comparison group were admitted for inpatient treatment with threatened preterm labour: 55 (30,6 %) patients – at 22-27 weeks of pregnancy, 79 (43,9 %) patients – at 28-33 gestation weeks, 46 (25,6 %) women – at 34-35 pregnancy weeks. Pregnant patients with threatened miscarriage underwent complex therapy according to standards of obstetrical and gynaecological care and clinical protocols approved by Ministry of health care of Ukraine (micronized natural progesterone in vaginal tablets by 50 mg twice per 24 hours during observation period due to clinical manifestations, tocolytics were drip-fed once per 24 hours during 24-48 hours in case of available marked uterine tone). Pregnant women of the group II with marked signs of maladaptation syndrome were administered phytometabolic preparation Cratal by 1 tablet thrice per 24 hours additionally. Excretion levels of adrenaline and noradrenaline ranged within the following margins (adrenaline: 52,1 ± 3,3 nmol/24 hours and noradrenaline: 61,2 ± 4,3 nmol/24 hours) in women who underwent phytometabolic therapy. Characteristic considerable decreasing of adrenaline excretion level was observed in 61 (76,2 %) cases, increased level was noticed in 19 (23,7 %) cases. Changes in serotonine level were more noticeable in blood of pregnant women after therapy with Cratal (serotonine level ranged in margins characteristic for the control group – 1,37 ± 0,06 mcmol/l). Decreasing serotoninergic system function was observed in 36 (45,0 %) patients, increased serotonine level was noticed in 31 (38,7 %) cases.